A polynomial algorithm for packing unit squares in a hypograph of a piecewise linear function - Arslanov Marat; Amirgalieva Zhazira; Kenshimov Chingiz (Open Engineering, 2017)
We consider the problem of packing the maximal number of unit squares in a hypograph of a function. A polynomial time algorithm is described to solve this problem for a piecewise linear function.